Outcome of external fixator in the treatment of intertrochanteric fracture in elderly patients with co-morbidities - Dutta, Deepak Kumar; Sinha, R, (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Incidence of intertrochanteric fracture is rising because of increasing number of elderly. They tend to have many comorbidities of different systems; therefore, major surgeries are not possible at times. In these patients, external fixator can be an option as it promotes early ambulation, thereby preventing recumbency-associated complications. Material and Methods: Elderly patients of interetrochanteric fracture and with medical comorbidities were managed with external fixator. Functional outcome was measured by Harris Hip Score (HHS) on first post-operative day and in follow ups on 4, 12, and 24 weeks. Results: Thrity patients (19 males, 11 females), of mean age 77.63 years (SD=9.06) were studied. HHS scores steadily increased from 37.6±5.28 on the first post-operative dayto 49.43±6.9 on 4 weeks, 59.83±7.17 on 12 weeks, and 72.47±4.17 on 24 weeks. The changes were all very highly significant (all p=0.000). Mean time taken to union was 14.67±2.28 weeks. None of the patients had recumbency-related complications. Conclusion: External fixators for intertrochanteric fractures in medically comorbid elderly patientsis effective in promoting ambulation and preventing recumbency-related complications.